2023
DOI: 10.3389/fimmu.2023.1107542
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiotherapy combined with systemic atezolizumab and bevacizumab in treatment of hepatocellular carcinoma with extrahepatic portal vein tumor thrombus: A preliminary multicenter single-arm prospective study

Abstract: Background and aimsThe efficacy and safety of systemic atezolizumab and bevacizumab (atezo/bev) in treatment of patients with unresectable hepatocellular carcinoma (HCC) have been demonstrated. However, the efficacy of this treatment in patients with HCC and extrahepatic portal vein tumor thrombus (ePVTT) is not satisfactory. This study aimed to study the efficacy and safety of combining intensity-modulated radiotherapy (IMRT) with systemic atezo/bev in treatment of these patients.MethodsThis multicenter prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Wang et al analyzed 30 patients with PVTT that were treated with a combination of ATE + BEV and radiotherapy. They reported that median OS and PFS were 9.8 and 8.0 months, and the ORR was 76.6% [23]. Manzar et al also analyzed the efficacy of 21 patients (of which 71.4% had PVTT) that were treated with a combination of ATE + BEV and radiotherapy; they reported that median OS was 16.1 months [24].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al analyzed 30 patients with PVTT that were treated with a combination of ATE + BEV and radiotherapy. They reported that median OS and PFS were 9.8 and 8.0 months, and the ORR was 76.6% [23]. Manzar et al also analyzed the efficacy of 21 patients (of which 71.4% had PVTT) that were treated with a combination of ATE + BEV and radiotherapy; they reported that median OS was 16.1 months [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, radiation therapy enhances antitumor T-cell response by stimulating effector phases, making it an excellent addition to PD-1 inhibitors 42 . Previous studies approved radiation plus PD-1 inhibitors therapy in HCC with PVTT 43,44 . Therefore, the combination therapy comprising lenvatinib, TACE, PD-1 inhibitor, and I 125 seed brachytherapy is expected to have a better therapeutic effect in the treatment of HCC, especially in patients with PVTT.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatment of HCC with vascular invasion is still a great challenge [ 6 , 38 ]. Our study found that TKI-I conferred a higher treatment response of tumor thrombosis compared with TKI alone.…”
Section: Discussionmentioning
confidence: 99%